2021
DOI: 10.4038/suslj.v19i1.7773
|View full text |Cite
|
Sign up to set email alerts
|

Language Alienation of Sri Lankan Students Studying Overseas: An Empirical Study

Abstract: Every year, a considerable number of Sri Lankan students migrate overseas to further their studies. In comparison to previous years, the total number of students emigrating has increased significantly. Especially, in such countries, many migrant students are able to find new opportunities for their career development other than furthering their education. This qualitative research aims to examine the language alienation of Sri Lankan students studying overseas and how it has hindered the achievement of their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A study conducted among Sri Lankan students studying overseas reported that the majority of the students ponder that they are weak in oral skills (Fazeena et al, 2012). In addition, a negative attitude towards a target language could create a boundary between the learner and the language (Pabodha & Abeywickrama, 2021). In this study, negative attitudes such as a lack of interest to participate in practice sessions were found among the respondents.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A study conducted among Sri Lankan students studying overseas reported that the majority of the students ponder that they are weak in oral skills (Fazeena et al, 2012). In addition, a negative attitude towards a target language could create a boundary between the learner and the language (Pabodha & Abeywickrama, 2021). In this study, negative attitudes such as a lack of interest to participate in practice sessions were found among the respondents.…”
Section: Discussionmentioning
confidence: 57%
“…Speaking in a second language triggers a feeling of unease (Pabodha & Abeywickrama, 2021). The process of learning is impeded by psychological elements including anxiety, fear, and negative attitudes (Seefa, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations